More wood but less biodiversity in forests in Finland: a historical evaluation - Mönkkönen Mikko; Aakala Tuomas; Clemens Blattert; Burgas Daniel; Duflot Rémi; Eyvindson Kyle; Kouki Jari; Laaksonen Toni; Punttila Pekka (Societas pro fauna et flora Fennica, 2025)
National forest inventories (NFI) in Finland provide empirical evidence for a marked increase in tree growth, total forest area, and total timber volume over the past century. Meanwhile, the assessments of threatened forest species and habitats indicate continuous degradation of biodiversity in Finnish forests. To shed light on this seeming paradox, we summarized the temporal patterns of forest characteristics (indicators) that have major influence on biodiversity, comparing the structure of current Finnish forests with natural and historical references. Using a variety of data sources, we estimated the proportion of area of old-growth forest and of deciduous-dominated forests, the density of large trees, and the amount of dead wood in Finnish forests under natural reference conditions, in the 1750s, 1920s (NFI1), and 2010s (NFI12). Our results show that levels of the forest structures essential to maintain ecologically diverse forests are below those that likely prevailed in Finland under natural reference conditions and in the 1750s. This scarcity is particularly pronounced for dead wood volumes and old forest area. The marked increase in the volume of living trees during the last century did not translate into improved biodiversity indicators and has not been effective for turning the tide of biodiversity loss in Finnish forests. We discuss actions that are necessary to safeguard forest biodiversity in Finland both in terms of protected areas and management in production forest.